PTU-048 A comparative qualitative survey of patient experience in barrett's oesophagus. Issue 2 (June 2019) - Britton, James; Taxiarchi, Paraskevi; Martin, Glen; Willert, Robert; Horne, Maria; Hamdy, Shaheen; McLaughlin, John; Ang, Yeng
Abstract : Introduction: This study aimed to assess Health Related Quality of Life (HRQoL) in patients with non-dysplastic Barrett's oesophagus (NDBO) and endoscopically treated dysplastic Barrett's oesophagus (DBO). Methods: This quantitative, self-administered questionnaire study was conducted across three NHS hospitals. Data was also collected from three other cohorts; GORD, colonic polyp surveillance and healthy individuals. HRQoL measurement included the Short Form-36 (SF-36), Gastrointestinal Symptom Rating Scale (GSRS), Hospital Anxiety and Depression Scale (HADS) and the Cancer Worry Scale (CWS). Fisher's exact and Spearman's rank correlation tests were used for analysis alongside propensity score matching to adjust for age, sex and comorbidities. Results: 797 participants responded to the survey (response rate 38%), of which 687 were eligible for analysis (NDBO n= 306, DBO n=49, GORD n= 132, Colonic polyps n= 152 and Healthy n=48). Mean SF-36 scores were significantly lower (worse) in the NDBO cohort compared to healthy controls across all 8 domains and both physical and mental component summary scores (p=0.009 – p=<0.001). 53% of NDBO participants reported significant cancer worry comparable to those treated for DBO (50%, p=0.933) and those undergoing colonic polyp surveillance (51%, p=0.355). Significantly less cancer specific worry was reported in GORD participants (43.4%, p=0.01). NDBO participants reported anxiety in 15.8% (n=48) and depression in 8.6% of cases which was statistically comparable to the other disease cohorts but higher than the healthy cohort (anxiety 4% p=0.001 and depression 0% p=0.006). Moderate-severe heartburn or acid regurgitation was found in 11% and 10% respectively in the NDBO cohort. This was comparable to the DBO cohort (heartburn 2% p=0.172, acid regurgitation 4% p=0.31) but significantly lower (better) than GORD participants (heartburn 31% p=<0.001, acid regurgitation 25% p=0.001). NDBO participants with moderate/severe GORD symptoms were associated with higher rates of anxiety (p=<0.001), depression (p=<0.001) and cancer specific worry (p=<0.001). Those who correctly perceived their cancer risk as low tended to have significantly lower rates of cancer worry (p=<0.001). Conclusions: This study provides a valuable insight into the problems BO patients may face. Based on these findings future care pathways must be more patient focused with greater reassurance and communication to address misconceptions of cancer risk, oesophageal cancer related worry and GORD symptom control.